Re-examination Of The Impact Of Economic Growth On Unemployment In Algeria Using Gordon’s Dynamic Law - Chahinez, Taleb Soumya; Si Mohammed, Kamel (University of Eloued جامعة الوادي, 2018)
The purpose of the present paper is to evaluate the effect of economic growth on unemployment, through both short and long-term and this within the Algerian economy during the 1985-2015 period. Gordon’s dynamic law was applied so as to achieve this purpose, this law requires separating unemployment and the general trend of the long-term economic growth rates, in order to respect this condition. Hodrick Prescott filter was used, this latter being one of the most important techniques that allow determining the long-term trend and how both GDP as well as unemployment rates vary around the natural rates. Thereafter, ARDL Bounds Testing Approach to Co-integration test was used, the research conducted that economic growth and unemployment tend to the same trend. Except during certain periods in which an inverse relationship between the two variables is noticed, which means that economic growth rates in Algeria do not diminish unemployment rates. As second step of the research, the causal relationship between the two variables using Granger Causality Test. The conclusion was the existence of causal relationship in the short-term from unemployment rates to gross domestic Product and this with a signification of 1%. The Cross Correlation Correlogam showed the existence of a major relationship between product rates and unemployment rates, during the period (T=0) the correlation being 75%. In addition to that product and unemployment rates are equal during this period
مجلة رؤى المجلد الثامن العدد الثاني
Keywords: : Economic Growth, Unemployment, HP filter, Gordon’s dynamic law, ARDL (JEL) Classification : E23,C32 .C22